Brain morphometry in adults with gambling disorder. (September 2021) - Bouchard, Amy E.; Dickler, Maya; Renauld, Emmanuelle; Lenglos, Christophe; Ferland, Francine; Rouillard, Claude; Leblond, Jean; Fecteau, Shirley
Abstract: Little is known regarding the brain substrates of Gambling Disorder, including surface brain morphometry, and whether these are linked to the clinical profile. A better understanding of the brain substrates will likely help determine targets to treat patients. Hence, the aim of this study was two-fold, that is to examine surface-based morphometry in 17 patients with gambling disorder as compared to norms of healthy individuals (2713 and 2790 subjects for cortical and subcortical anatomical scans, respectively) and to assess the clinical relevance of morphometry in patients with Gambling Disorder. This study measured brain volume, surface and thickness in Gambling Disorder. We compared these measures to those of a normative database that controlled for factors such as age and sex. We also tested for correlations with gambling-related behaviors, such as gambling severity and duration, impulsivity, and depressive symptoms (assessed using the South Oaks Gambling Screen, years of gambling, Barratt Impulsiveness Scale, and Beck Depression Inventory, respectively). Patients displayed thinner prefrontal and parietal cortices, greater volume and thickness of the occipital and the entorhinal cortices, and greater volume of subcortical regions as compared to the norms of healthy individuals. There were positive correlations between surface area of occipital regions and depressive symptoms. This work contributes to better characterize the brain substrates of Gambling Disorder, which appear to resemble those of substance use disorders and Internet Gaming Disorder. Graphical abstract: Image 1 Highlights: Patients with Gambling Disorder had thinner prefrontal and parietal cortex. Patients had greater volume and thickness of the occipital and entorhinal cortex. They also had greater volume of subcortical regions. This study complements previous literature by using a whole-brain approach.